2015
DOI: 10.1016/j.plasmid.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The Xis2d protein of CTnDOT binds to the intergenic region between the mob and tra operons

Abstract: CTnDOT is a 65kbp integrative and conjugative element (ICE) that carries genes encoding both tetracycline and erythromycin resistances. The Excision operon of this element encodes Xis2c, Xis2d, and Exc proteins involved in the excision of CTnDOT from host chromosomes. These proteins are also required in the complex transcriptional regulation of the divergently transcribed transfer (tra) and mobilization (mob) operons of CTnDOT. Transcription of the tra operon is positively regulated by Xis2c and Xis2d, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“… 2013a , Ringwald and Gardner 2015 ). Xis2c and Xis2d are essential for the excision of CTn DOT and bind to attL and attR (Hopp, Gardner and Salyers 2015 ). Exc is a topoisomerase III essential to excision (Sutanto et al.…”
Section: Experimental Model Ices: Mechanisms and Regulationmentioning
confidence: 99%
“… 2013a , Ringwald and Gardner 2015 ). Xis2c and Xis2d are essential for the excision of CTn DOT and bind to attL and attR (Hopp, Gardner and Salyers 2015 ). Exc is a topoisomerase III essential to excision (Sutanto et al.…”
Section: Experimental Model Ices: Mechanisms and Regulationmentioning
confidence: 99%
“…These two proteins bind DNA in a sequence‐specific manner, but their binding sites are strikingly different. While Xis2d binds a single region of dyad symmetry (Hopp et al ., ), Xis protein from P22 binds cooperatively to four 6 bp direct repeats separated by 4 bp spacers. It was shown that both proteins bend DNA, and the bending induced by the Xis2d protein is important for transcriptional activation of nearby mob operon (Hopp et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, for these ICEs the excisionase has been found to act as a transcription factor, activating the expression of downstream genes required for the transfer of the elements. This indicates that ICEs of the Mesorhizobium spp., may use a similar method of regulation observed for CTn DOT of Bacteroides thetaiotamicron , in which the excisionases moonlight as transcription factors, activating the expression of genes needed for conjugative replication, thereby directly linking Xis to the regulation of replication [44,45].…”
Section: Discussionmentioning
confidence: 99%